Worldviews and values in higher education : teaching, learning, curricula, and assessment - Rao, Madasu Bhaskara; Singh, Abhilasha; Rao, Pulaparthi Mallika (Emerald Publishing Limited, 2024)
Launching the Global Perspectives on Higher Education Development series, editors Madasu Bhaskara Rao, Abhilasha Singh and Pulaparthi Mallika Rao introduce the concept of values and the role they play in the emerging university of the twenty-first century. How do universities' missions, visions, policies, and strategies shape their responses to a world that is swiftly changing due to increased globalisation, demand, competition, and innovation? Understanding that educational stakeholders must comprehend the nature of societal culture and communal values and the role they play in shaping, often implicitly, a university's ethos and traditions, contributors explore how values operate at an institutional level. How do they impact micro-level practises, such as pedagogical strategies, academic achievement, curriculum development, and evaluation? Providing a much-needed global perspective-based analysis of the issue of educational values, this first volume on Worldviews and Values in Higher Education examines how higher education cultures are embedded within and heavily influenced by national cultures, norms, and structures through the lenses of Teaching, Learning, Curricula, and Assessment.
Includes index.
Keywords: Education, Higher.; Education, Schools, Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books